COMPARATIVE EVALUATION OF EFFICACY OF PURE COLLAGEN TYPE I BASED MODERN DRESSING WITH CONVENTIONAL DRESSING IN THE TREATMENT OF BURN AND DIABETIC FOOT ULCER. - Khemariya, Richa; Khemariya, Prashant (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
Aim: To evaluate the significance of introducing an absorbable collagen type-I dressing in the management of Burn wound and Diabetic Foot wound. Background: A wound may be explained in numerous ways; either by its etiology, by anatomical location, by whether it is acute or chronic, by the method of closure, by its presenting symptoms or indeed by the appearance of the predominant tissue types in the wound bed. The variety of wound types have resulted in a wide range of wound dressings. In order to offer the most excellent treatment options, these challenges need to be identified and overcome by using the most appropriate dressings and treatment regimens available. Methods: Total no. of 41 Patients was treated with SkinTempTM II and MedifilTM II. Case report from (CRF) is an observation study data that was undertaken on injured patients with a variety of wound types are presented. Patients were classified in to two groups “HBS-SRK Group” and “Conventional Group”. Results: The beginning of dressings with SkinTempTM II and/ or MedifilTM II was linked with fall in pain during the surgery and re-dressing. The standard duration for appearance of in good physical shape of granulation tissue over the wounds that were treated with collagen dressing (SkinTempTM II and MedifilTM II) was 8-12 days while conventional dressing took more than 30 days for same granulation formation